REPRESENTASI DALAM LIRIK LAGU PEREMPUAN ANALISIS WACANA KRITIS SARA MILLS - Alfi Tri Rosita; Dzarna Dzarna; Eka Nova Ali Vardani (Program Studi Pendidikan Bahasa dan Sastra Indonesia, FKIP, Universitas Halu Oleo Kampus Bumi Tridharma Andounohu Kendari, Provinsi Sulawesi Tenggara – Indonesia, 2025)
The purpose of writing this article is to identify forms of language use in song lyrics that represent women with negative images, as well as to reveal the meaning contained in the song lyrics. This research is descriptive qualitative research using note-taking and documentation techniques as the collection method. This research data was taken from three songs sung by women, namely the songs Tenang, Takut, and Tak Segampang Itu. The analytical method in the research used Sara Mills' Critical Discourse Analysis in the subject-object position and found depictions of women with negative images in the form of passivity, dependence, and dominance in the subject position. Where, women themselves tell or interpret the sad events, betrayal, feelings of pressure, domination that they experience. Meanwhile, men or powerful groups are in the position of the object or person being told. Even though they are positioned as objects, men or dominant groups are described as having great power, authority or influence over women.